A Study of Financial Literacy Level towards Electronic Banking Amongst Youth - Dr. Meghna Jain (HM Journals, 2023)
Literacy towards various financial aspects as well as towards financial instruments has been very low among people in many countries including developed and developing countries. Financial literacy can be considered very low among youth as the outcome of most of the research. There are many options where people can invest their money. Such options are known to only a few common people. Every individual starts saving money at a very early age. This money reaches banks only after the person crosses a certain age. Even today, people are using traditional methods of Banking as they are not aware about E-Banking to a great extent. E-Banking helps the customers in saving their money, efforts and time. Bankers try to educate them about various uses of E-Banking from time to time through various seminars, educational programmes and many other ways. In this research, students at a major institution were randomly chosen to participate in research. The questions were typically based on the use of E-Banking services and also to check whether they are still connected with Banks through traditional methods only. The objective of the study is to understand the awareness level and usage towards various E-banking services offered by Public and Private Sector Banks amongst youth. The result of the study indicates that the youth has been using ATM and Internet Banking, but is still not aware much about the other forms of E-Banking i.e. Mobile, SMS and Phone Banking.